2020
DOI: 10.1096/fj.202001152r
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin regulates 14‐3‐3ζ mRNA and promotes cofilin phosphorylation to induce tunneling nanotube formation

Abstract: Tunneling nanotubes (TNTs) mediate intercellular communication between animal cells in health and disease, but the mechanisms of their biogenesis and function are poorly understood. Here we report that the RNA-binding protein (RBP) nucleolin, which interacts with the known TNT-inducing protein MSec, is essential for TNT formation in mammalian cells. Nucleolin, through its RNA-binding domains (RBDs), binds to and maintains the cytosolic levels of 14-3-3ζ mRNA, and is, therefore, required for TNT formation. A sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
10
0
3
Order By: Relevance
“…Similarly the endocytosis of HIV (human immunodeficiency virus) and HSV (herpes simplex virus) viruses via PAK dependent route induces the biogenesis of TNTs (Van den Broeke et al, 2009;Mukerji et al, 2012;Jacob et al, 2015;Jansens et al, 2020). Furthermore, cofilin an actin-binding protein, a downstream signaling cascade of PAK1, modulates F-actin polymerization and biogenesis of TNTs (Dagar et al, 2021). In our recent study, we have observed that the Aβ induced membrane damage instigates PAK1 dependent endocytosis and coupled lysosomal exocytosis to repair the membrane.…”
Section: Actin Cytoskeleton Regulatory Pathways In the Biogenesis Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly the endocytosis of HIV (human immunodeficiency virus) and HSV (herpes simplex virus) viruses via PAK dependent route induces the biogenesis of TNTs (Van den Broeke et al, 2009;Mukerji et al, 2012;Jacob et al, 2015;Jansens et al, 2020). Furthermore, cofilin an actin-binding protein, a downstream signaling cascade of PAK1, modulates F-actin polymerization and biogenesis of TNTs (Dagar et al, 2021). In our recent study, we have observed that the Aβ induced membrane damage instigates PAK1 dependent endocytosis and coupled lysosomal exocytosis to repair the membrane.…”
Section: Actin Cytoskeleton Regulatory Pathways In the Biogenesis Of ...mentioning
confidence: 99%
“…Role of cofilin has recently been reported in the biogenesis of TNT. A recent study by Dagar et al (2021); suggests that, in addition to cofilin-regulated actin modulation, the exocyst complex protein, M-sec dependent recycling of membrane needs to function in a cohort, as a necessary step in the biogenesis of TNTs. RNA-binding protein nucleolin interacts with M-sec, while nucleolin regulates 14-3-3ζ mRNA, which is also required for the formation of TNT.…”
Section: Actin Regulatory Pathways In Intercellular Spread and Alzhei...mentioning
confidence: 99%
“…Após a descoberta dos nanotubos de tunelamento, eles foram observados em vários tipos celulares (in vitro) como: células imunes (71,(74)(75)(76), células renais (69,77), células epiteliais (78,79), células tumorais (80)(81), neurônios e astrócitos (82)(83)(84). Em células T Jurkat, nanotubos são capazes de conectar cerca de 15% das células em condições normais de cultura, sendo então um ótimo modelo de estudo para estas estruturas (85).…”
Section: Nanotubos De Tunelamentounclassified
“…The actin-binding ability of the protein is modulated by phosphorylation of βCamKII [ 117 ]. Inactivation of cofilin by the RNA-binding protein nucleolin induces TNT biogenesis [ 118 ]. In addition, the alphaherpesvirus-induced biogenesis of TNTs depends on the US3 protein kinase-mediated activation of p21-activated kinases (PAKs) apparently by activation of Cdc42/Rac1 and Rho signalling axis, within a poorly understood complex mechanism [ 32 ].…”
Section: Rho Gtpase Related Signals Counteract Apoptosis Via Tunnelling Nanotubesmentioning
confidence: 99%
“…Altogether, these studies suggest a complex regulatory mechanism of Rho GTPases in TNT biogenesis. A further recent report [ 118 ], has also shown that M-sec regulated exocyst complex needs to function together with actin polymerization by inhibiting activity of cofilin in the biogenesis of TNTs in multiple mammalian cellular models. The study suggests that in addition to actin polymerization, M-Sec-dependent plasma membrane (PM) re-modelling is a necessary step in formation of TNTs.…”
Section: Rho Gtpase Related Signals Counteract Apoptosis Via Tunnelling Nanotubesmentioning
confidence: 99%